Podróże śladami Michaiła Bułhakowa i bohaterów jego powieści w wybranych polskich artykułach prasowych - Korcz, Karolina (Slavia Occidentalis, 2011)
The text is devoted to special testimonies of the reception of Mikhail Bulgakov’s novel The Master and Margarita. The author of the summary concentrates on the phenomenon of organizing special trips to follow the favourite writer and the characters known from his literary works. She seeks the motivations for embarking on such journeys. The author develops a thesis that the interests in the places connected with the life and literary output of Mikhail Bulgakov assumed massive scale and resulted from genuine aesthetic experience of the readers.